2009
DOI: 10.1007/s12206-009-0919-x
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for smart functionally graded beam integrated with shape memory alloy actuators

Abstract: This paper presents a theoretical study of the thermally driven behavior of a shape memory alloy (SMA)/FGM actuator under arbitrary loading and boundary conditions by developing an integrated mathematical model. The model studied is established on the geometric parameters of the three-dimensional laminated composite box beam as an actuator that consists of a functionally graded core integrated with SMA actuator layers with a uniform rectangular cross section. The constitutive equation and linear phase transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The above analysis suggests that the area of hysteresis loop can achieve the maximum when the phase transformation parameters meet a certain relationship (9). That is to say that the perfect damping effect can be obtained through choosing SMA material with suitable parameters.…”
Section: From the Equationmentioning
confidence: 94%
See 1 more Smart Citation
“…The above analysis suggests that the area of hysteresis loop can achieve the maximum when the phase transformation parameters meet a certain relationship (9). That is to say that the perfect damping effect can be obtained through choosing SMA material with suitable parameters.…”
Section: From the Equationmentioning
confidence: 94%
“…They have been widely applied in mechanical engineering, civil engineering, aerospace engineering and so on [1][2][3][4][5][6]. At present, in the static and dynamic analysis of engineering structure, research on SMA composite structure mainly involves active and passive control of the deformation, vibration and noise of the beam and shell structure, of which the main composite structures adopted are: (1) SMA films are laminated with a substrate [6][7][8][9][10]; (2) SMA wires and alloying pellets are embedded into a substrate [11,12]; (3) SMA fiber woven layer composite structures [13]. For the first laminated structure, the SMA is usually used as a surface, while the other elastic material is used as a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Birman [21] proposed the advantage of the sinusoidal distribution of SMA fibers that results in a significant increase in the buckling load. Sepiani et al [22] found that changes in the thermally driven behavior of a shape memory alloy (SMA)/FGM actuator's responses during phase transformation due to strain recovery are significant. Asadi et al [23] and Babaee et al [24] both studied the nonlinear thermal buckling of an SMA layer and a functionally graded beam/plate on nonlinear elastic foundation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not provide analytical derivations for the moment-curvature relations. Another model based on the Euler-Bernoulli theory was proposed by Sepiani et al (2009) considering a variety of thermal loading cases. However, the authors assumed piece-wise linear moment and strain relations and considered the beam behavior during monotonic loading only.…”
Section: Introductionmentioning
confidence: 99%